Leśmianowska , ontologia" nicości - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 1998)
The aim of the article is to present the senses ant contexts in which the concept of nothingness (and also "non-existence", "emptiness", a "vacuum” and "timelessness") appears in the world presented in Bolesław Leśmian’s poems. The above-mentioned terms are the constructive elements of his poetic reality. The lyric "I" of Leśmian’s numerous poems is the poet, placing the world of his poetry on the borderland between existence and non-existence. Paradoxically, one might say that the poet has created a world which does not exist, though it is characterized by some specific qualities. Thus, there is no clear borderline between existence and nothingness. In the world presented by Bolesław Leśmian, absolute nothingness appears to be impossible. One can, however, identify a kind of transcendental nothingness, which is not the complete annihilation of everything, but only, as the poet put it, "a state of consciousness different from the consciousnes of existence". There is also a category of immanent nothingness, which can be perceived either as a lack in existence (this sort of nothingness is typical of the protagonist from Pieśni kalekujące [The Crippling Songs] or as the annihilation of individual existence. The second type of nothingness is frequently identified with non-existence. The concepts discussed here have been reified and materialized by the poet. They have become the agent or subject of action. Sometimes they are presented as the categories of space. Then their synonyms are "emptiness", a "vacuum" and a "chasm" existing in timelessness. Nothingness is a category which, in the poems by Leśmian, defines not only the ontological status of all kinds of existence but also the drama of the existential situation of characters living in the poetic world presented in the poems.